2013
DOI: 10.1007/s00423-013-1071-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of transvaginal/transumbilical versus classical laparoscopic cholecystectomy—an analysis of 88 patients

Abstract: This long-time prospective data acquisition from 88 or, for some data, 61 patients accounts for the safety of TVC, particularly with regard to sexual function. Additionally, it found less postoperative impairment, quicker recovery and improved satisfaction for TVC as compared to LC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 21 publications
1
22
0
2
Order By: Relevance
“…Aesthetic outcome, measured using a cosmetic scale ranging from 3 (lowest level of satisfaction) to 24 (highest level of satisfaction), was reported by three RCTs and three non‐randomized trials. Patients in the hybrid NOTES group had a higher score on the cosmetic scale than patients in the standard laparoscopy group (MD 1·14, 95 per cent c.i.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aesthetic outcome, measured using a cosmetic scale ranging from 3 (lowest level of satisfaction) to 24 (highest level of satisfaction), was reported by three RCTs and three non‐randomized trials. Patients in the hybrid NOTES group had a higher score on the cosmetic scale than patients in the standard laparoscopy group (MD 1·14, 95 per cent c.i.…”
Section: Resultsmentioning
confidence: 99%
“…A lower wound infection rate was found for hybrid NOTES in this meta‐analysis. It may be assumed that the rate of incisional hernia is lower after hybrid NOTES, but few studies have reported on this outcome. Given the low incidence of trocar site hernia, a very high sample size would be needed to demonstrate a possible reduction in incisional hernia by NOTES.…”
Section: Discussionmentioning
confidence: 99%
“…Bei der Analyse der gleichen Kollektive fand sich zudem im Langzeit-Follow-up kein Nachteil bezüglich der weiblichen Sexualfunktion [6], sodass wir die Technik auf die Appendektomie übertru-gen und diese weiblichen Patienten bei entsprechender Indikation seit Mai 2012 anboten.…”
Section: Diskussionunclassified
“…Several groups have attempted to standardize patient selection criteria for THNC in order to achieve safe and effective clinical outcomes [4,14,18,36,37]. However, there is not an official consensus defining these criteria.…”
Section: Patient Selection (Preoperative Evaluation)mentioning
confidence: 99%
“…Despite the increased number of clinical studies confirming the advantages and benefits of THNC [4,8,12 •• , 21, 22 • , 29], it is still considered an investigational surgical approach in many aspects, and surgeons still have concerns regarding the safety of this procedure in terms of sexual function and future fertility [30-33, 34 • , 35]. The objective of this article is to review this surgical technique and its clinical outcomes based on the current scientific evidence available in the literature.…”
Section: Introductionmentioning
confidence: 99%